Linguocultural Analysis Of Some Onomastic Units In Togay Murad's Work "The Fields Left From My Father" - Sh. Rakhmatullayev; Sh. Tokhtayev (Zien Journals, 2025)
This article analyzes the semantics of some anthroponyms in Togay Murod's work "The Fields Left by My Father", its linguo-cultural study. It analyzes the environment of the period in which the events took place, the character traits of people, and the way their worldview is reflected in the name. The article presents evidence about the attitude of the heroes of the work to the class that adopted the name, as well as the motive and basis for their naming
Keywords: onomastics; anthroponym; name